Unclogged Janus Mesh for Fog Harvesting - Lee, Joo Hee; Lee, Young Jin; Kim, Ho-Young; Moon, Myoung-Woon; Kim, Seong Jin (American Chemical Society, 2022)
Janus membranes with asymmetric surface wettability have been extensively utilized in various fields, including fog harvesting, because of their novel liquid transport properties. However, Janus membranes have an inherent disadvantage in terms of aerodynamic efficiency in harvesting fog because of the clogged water bridges caused by the small pore size. In the present work, we applied Janus wettability to mesh geometry with systematically varying hole sizes. For a clogged mesh with a small hole size, capillary water transport to the mesh back via the wettability gradient in the direction of fog flow helps harvest more fog by enhancing water drainage, similarly to the Janus membrane. The advantage of the capillary water transport extends to a clog-free mesh with larger hole sizes but more preferably to a Janus mesh with a superhydrophilic back, which presents the highest level of fog-harvesting yield because of the fast shedding frequency and short onset time. In contrast, a Janus mesh with a superhydrophobic front, which also has a wettability gradient along the fog flow, produces a lower fog-harvesting performance, particularly at slow fog speeds, because of the dropwise deposition of large water drops that locally disturb fog flow around a protruding water surface. On the other hand, the other type of Janus mesh with a superhydrophilic front is observed to minimize this disadvantage in the local fog flow by virtue of the filmwise deposition. It is also found that some Janus treatments can help protect mesh holes from clogging up by either forming a thin water meniscus or resisting water transport through the mesh holes.